Conflict in lebanese banks toward lifting banking secrecy. BOD members vs Compliance managers - Y. HAMDAR, Ghinda (Proche-Orient Études en management, 2019)
This paper aims to explore potential conflict of interest between BOD members and compliance managers in Lebanese banks while facing the international pressure of transparency that oppresses banking secrecy worldwide.